Mushroom: a potent source of natural antiviral drugs - Raut, Jay Kant (Applied Science and Technology Annals, 2020)
Emerging viral infections such as the zika virus, dengue virus, ebola virus, corona virus are afflicting millions of human populations worldwide. Therefore, the development of new treatments against emerging infectious diseases has become an urgent task. The availability of commercially viable, safe, and effective antiviral drugs still remains a big challenge. Mushrooms are considered as an untapped reservoir of several novel compounds of great value in industry and medicine. Although exploration, and exploitation of the therapeutic importance of fungal metabolites has started early with the discovery of penicillin, mushrooms’s pharmacological potential has much less been investigated. This article briefly reviews the antiviral potentials of mushrooms to combat deadly disease outbreaks caused by emerging and re-emerging viruses. Altogether 69 mushroom species with potent antiviral agents and mode of action against prominent viruses such as human immunodeficiency virus, influenza, herpes simplex virus, hepatitis B and C viruses, corona viruses etc. are listed in this study. Further studies are encouraged to discover more novel potent antiviral agents or evaluate already known compounds from those mushrooms with clinical trials.